Reduction-Responsive Molecularly Imprinted Poly(2-isopropenyl-2-oxazoline) for Controlled Release of Anticancer Agents - Michał Cegłowski; Valentin Victor Jerca; Florica Adriana Jerca; Richard Hoogenboom (MDPI AG, 2020)
Trigger-responsive materials are capable of controlled drug release in the presence of a specific trigger. Reduction induced drug release is especially interesting as the reductive stress is higher inside cells than in the bloodstream, providing a conceptual controlled release mechanism after cellular uptake. In this work, we report the synthesis of 5-fluorouracil (5-FU) molecularly imprinted polymers (MIPs) based on poly(2-isopropenyl-2-oxazoline) (PiPOx) using 3,3'-dithiodipropionic acid (DTDPA) as a reduction-responsive functional cross-linker. The disulfide bond of DTDPA can be cleaved by the addition of tris(2-carboxyethyl)phosphine (TCEP), leading to a reduction-induced 5-FU release. Adsorption isotherms and kinetics for 5-FU indicate that the adsorption kinetics process for imprinted and non-imprinted adsorbents follows two different kinetic models, thus suggesting that different mechanisms are responsible for adsorption. The release kinetics revealed that the addition of TCEP significantly influenced the release of 5-FU from PiPOx-MIP, whereas for non-imprinted PiPOx, no statistically relevant differences were observed. This work provides a conceptual basis for reduction-induced 5-FU release from molecularly imprinted PiPOx, which in future work may be further developed into MIP nanoparticles for the controlled release of therapeutic agents.